Wilfred Cantwell Smith’s Concept of Religion: An Islamic Appraisal - Ayesha Qurrat ul Ain (Journal of Islamic Thought and Civilization, 2021)
In the vein of many Western scholars of comparative religions, Wilfred Smith also realizes the difficulty implicated in defining religion but he is unique in daring to call for discarding religion, arguing that the concept is inadequate. According to him, the inadequacy of the concept leads to the intellectual dilemma of the relation between many religious traditions and the One Ultimate Reality, the historical change and abiding truth, the world and God. The solution to such a dilemma is to revise the categories of intellectual discourse in the field of theology/religious studies and move towards a better alternative. These alternatives should aim to depict human religious life in a more adequate and universal way. Hence, Smith suggests splitting the esoteric and exoteric dimensions of religion and proposes for them the categories of faith and cumulative tradition respectively. Primarily, this research seeks to explore the significance of Smith’s critique of religion as well as the practicality and utility of the alternative categories i.e., faith and cumulative tradition in the modern global scenario from an Islamic perspective.